Johtamisviestintä digitaloudessa - Hirsto, Heidi; Porttikivi, Merja (VAKKI ry, 2019)
Leadership communication and management communication are research areas that draw upon many neighboring disciplines and traditions but also share some common defining characteristics. In this article, we delineate and organize this field of research with the aim of arriving at a multifaceted and broad-based description of leadership/management communication especially in digital media environments. Drawing on research literature and empirical examples from symposium presentations, we show that research in this area addresses leadership communication on both private and public arenas, and from the viewpoints of both communicative action and cultural representation. We introduce a grid of leadership/management communication research that is designed to include a wide array of research ranging from social media influence to workplace communication and media representations.
Keywords: digitalisaatio; johtamisviestintä; organisaatioiden diskurssit; organisaatioiden viestintä; yritysviestintä; fi=Viestintätieteet|en=Communication Studies|